Об одном неравенстве из теории приближения - Леончик, Е.Ю. (Український математичний журнал, 2003)
Досліджується одна нерівність з теорії наближення. Отримано необхідну та достатню умови, коли ця нерівність має місце, та наведено приклади, які свідчать про остаточність результатів. We investigate one inequality in approximation theory and obtain necessary and sufficient conditions for the validity of this inequality. We present several examples demonstrating that the results obtained are unimprovable.